Characteristics of Crispy Brownies from Diversified Arrowroot Starch and Black Soldier Fly Larvae (BSFL) Flour and its Potential as a Snack Food for Stunting - Dewi, I Gusti Agung Bulan Mutiara; Putra, I Gede Arie Mahendra (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Stunting is a condition regarding malnutrition, especially in children, which can cause a child to experience slow growth, decreased muscle mass, and weight loss. Protein is one of the important nutrients consumed by children so as not to cause stunting. High protein consumption is the most appropriate step to improve nutrition in stunted children. One of the ingredients high in protein content is Black Soldier Fly Larvae (BSFL) flour. This study aims to determine the characteristics of crispy brownies resulting from the diversification of arrowroot starch and BSFL flour and its potential as a snack for stunted patients. The design used in this study was a Randomized Group Design with treatment of the ratio of arrowroot starch and BSFL flour consisting of five treatment levels, namely (50:5), (50:10), (50:15), (50:20), and (50:25). The parameters observed were sensory characteristics and the best treatment followed by testing protein content, moisture content, ash content, fat content, carbohydrate content and energy. The results showed that the best treatment of sensory characteristics was obtained in the treatment of the ratio of arrowroot starch and BSFL flour (50:10) with sensory properties of color attributes 4.44 (like), aroma 3.94 (somewhat like), texture 4.38 (like), taste 4.19 (like), and overall acceptance 4.38 (like) with water content 1.37%, ash content 1.95%, protein content 8.04%, fat content 21.48%, carbohydrates 67.16%, and energy 494.14 Kcal. The developed diversified crispy brownie product also has the potential as a distraction food for stunting sufferers. It is expected to be a development in utilising local food ingredients combined with insects to support food security in Indonesia.